Wanderfund (a personalized travel fund) / Ardini Athirah Jamaluddin ... [et al.] - Jamaluddin, Ardini Athirah; Rahman, Nabilah Izzati; Rozie, Nur Amiera Rosyada; Habib Alnsar, Nur Athirah; Hashim, Nurhaslinda (Universiti Teknologi MARA, Kedah, 2023)
Wanderfund is an application that enables users to plan their travel fund. This application provides numerous features that will help the users to set their travel goals and plan the right strategies to achieve it. These days, the inflation rate keep on increase due to economy changes and it is directly affecting individual budget including personal fund for travel and vacation. At the same time without any assistance and proper planning, makes people become more stress to save money for travel because it is difficult for them to accomplish their travel goals as the cost and economy situation always changing. Nonetheless, the objective of our innovation is to a user’s to effectively managing their money thus makes everyone have a chance to travel around the globe. In addition, the main novelty of this application is it has personalized budgets for travellers to set up their goals within their own timeframe. It also has all-in-one travel setlist such as a travel calculator, currency converter, list of interesting places to visit, lists of verified travel agencies and personalized statistics of users travel fund. In addition, there is one feature specifically design for the travel agencies to promote their travel plans and services which include activities, places to visit, restaurants, and itineraries. The main benefit of Wanderfund is users can find a complete checklist as it provides all the necessary travel information in one application based on their own budget and preference, thus making it easy for users to plan, manage time and organize their trip effectively.